RAGAM BAHASA DALAM KONTEN YOUTUBE FUTSAL TALK BOLALOB DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA - Hendra Saputra; Muhammad Alipia (Universitas Lampung, 2021)
The problem in this study is the variety of languages on the content of YouTube futsal talk Bolalob and its implications for Indonesian language learning. This research uses descriptive methods. The source of this research data is a futsal talk video download from YouTube. The results of this study were found two varieties of languages, which are various terms of use language and a variety of formalized languages. The results of this study can be implied by the study of Indonesian language in high school to be used as teaching materials on the material to control the lecture text.Masalah dalam penelitian ini ialah ragam bahasa pada konten youtube futsal talk bolalob dan implikasinya terhadap pembelajaran bahasa Indonesia. Penelitian ini menggunakan metode deskriptif. Sumber data penelitian ini adalah video futsal talk unduhan dari youtube. Hasil penelitian ini ditemukan dua ragam bahasa, yaitu ragam bahasa segi pemakaian dan ragam bahasa segi keformalan. Hasil penelitian ini dapat diimplikasikan terhadap pembelajaran bahasa Indonesia di sekolah menengah atas untuk dijadikan bahan ajar pada materi mengontruksi teks ceramah.Keywords: language variations, futsal talk, implications.DOI Artikel: https://doi.org/10.23960/J-Simbol/v9i1.2021.9